Optimizing fast first pass complete reperfusion in acute ischemic stroke - the BADDASS approach (BAlloon guiDe with large bore Distal Access catheter with dual aspiration with Stent-retriever as Standard approach) - Ospel, J M; Volny, O; Jayaraman, M; McTaggart, R; Goyal, M (Expert review of medical devices, 2019)
Introduction: Endovascular therapy is the standard of care for acute ischemic stroke due to large vessel occlusions. The ultimate goal is to achieve fast first pass complete reperfusion, since delayed and/or incomplete reperfusion increases complication rates and costs and deteriorates patient outcome. Achieving optimal results can sometimes be challenging, particularly in patients with tortuous vessels. Several techniques have been described lately to optimize recanalization, including first line aspiration and various stent-retriever assisted techniques. In our experience, mechanical thrombectomy with a BAlloon guide catheter, large bore Distal access catheter, Dual Aspiration and Stent-retriever as Standard approach (BADDASS) is the most efficient technique to succeed, since it combines the advantages of stent-retrievers and distal aspiration.Areas covered: The purpose of this review is to enable neurointerventionalists to achieve fast first pass complete reperfusion by outlining the BADDASS approach step-by-step and sharing additional tips for navigating through challenging internal carotid artery segments.Expert opinion: In our experience, the BADDASS approach is the safest and most effective way to achieve fast first pass complete reperfusion.
Keywords: stenty; thrombectomy; ischemie mozku; Brain Ischemia; Humans; balloon guide catheter; endovascular therapy; Stroke; lidé; odsávání; reperfusion; ischemic stroke; reperfuze; cévní mozková příhoda; Stents; Reperfusion; Aspiration; srdeční katetrizace; Cardiac Catheterization; Suction